Efektivitas Media Tanam Berbasis Tongkol Jagung (Zea mays L.) dan Dedak terhadap Pertumbuhan dan Produksi Jamur Merang (Volvariella volvacea L.) - Elana Febriani; Ervina Titi Jayanti; Firman Rahman (Yayasan Tajuk Indonesia, 2025)
Straw mushroom (Volvariella volvacea L.) is a mushroom that has a volva or cup, pink spores, and a stem. This study aims to determine the effect of the composition of corn cob (Zea mays L.) and bran planting media on the growth and production of straw mushroom (Volvariella volvacea L). This study was conducted for 14 days calculated from the day of mixing. The tools in this study were burlap sacks, plastic, wooden boards, nails, plywood, hammers, water hoses, rulers/meters, calipers, thermometers, cameras, stationery, plastic bags, and markers, while the materials were corn cobs, bran, urea, yeast, and water. The method used in this study was an experiment and the design used was a randomized block design with 5 treatments, 1 control, and 5 repetitions. The composition of the planting media comparison includes: P₀ (control), P₁ (55% corn cob: 45% bran), P₂ (65% corn cob: 35% bran), P₃ (75% corn cob: 25% bran), and P₄ (85% corn cob: 15% bran). The results of the study showed that the composition of the planting media greatly influenced the growth and production of straw mushrooms as seen from the significant values ​​of all treatments of more than 5%. The best results for all treatment parameters were obtained by the P₁ (55%: 45%) and P₂ (65%: 35%) treatments.